Low Impedance Multi-Decade Integrated Amplifier for EMR Measurements in Fully Electric Vehicles - Chicharro, José Antonio; Weigel, Robert; Fischer, Georg; Ußmüller, Thomas (Asia-Pacific International Symposium and Exhibition on Electromagnetic Compatibility, 2013)
This paper reports on the design, simulation and measurement of a low-impedance broadband integrated amplifier in bipolar technology (Infineon’s B7HF200). Aimed to serve as a LNA for an inductive field probe operating in the frequency range 5 kHz - 6 GHz, the amplifier is designed to offer a good performance with a purely resistive 10-Ohm power source. A nominal gain of 30 dB up to 1 GHz (15 dB at 6 GHz) and and input scattering parameter s11 of -10 decibels are achieved. Power consumption is 30 mW. Limitations of and improvements for this design are discussed.
elib2cris::1512001600,chicharro2013
Keywords: Bipolar; Integrated circuits; broadband amplifier; low-impedance LNA; EMR measurements; multi-decade